Endothelial-to-Mesenchymal Transition in Human Adipose Tissue Vasculature Alters the Particulate Secretome and Induces Endothelial Dysfunction. Issue 10 (October 2019) - Haynes, Bronson A.; Yang, Li Fang; Huyck, Ryan W.; Lehrer, Eric J.; Turner, Joshua M.; Barabutis, Nektarios; Correll, Vanessa L.; Mathiesen, Allison; McPheat, William; Semmes, O. John; Dobrian, Anca D.
Abstract : Objective: Endothelial cells (EC) in obese adipose tissue (AT) are exposed to a chronic proinflammatory environment that may induce a mesenchymal-like phenotype and altered function. The objective of this study was to establish whether endothelial-to-mesenchymal transition (EndoMT) is present in human AT in obesity and to investigate the effect of such transition on endothelial function and the endothelial particulate secretome represented by extracellular vesicles (EV). Approach and Results: We identified EndoMT in obese human AT depots by immunohistochemical co-localization of CD31 or vWF and α-SMA (alpha-smooth muscle actin). We showed that AT EC exposed in vitro to TGF-β (tumor growth factor-β), TNF-α (tumor necrosis factor-α), and IFN-γ (interferon-γ) undergo EndoMT with progressive loss of endothelial markers. The phenotypic change results in failure to maintain a tight barrier in culture, increased migration, and reduced angiogenesis. EndoMT also reduced mitochondrial oxidative phosphorylation and glycolytic capacity of EC. EVs produced by EC that underwent EndoMT dramatically reduced angiogenic capacity of the recipient naïve ECs without affecting their migration or proliferation. Proteomic analysis of EV produced by EC in the proinflammatory conditions showed presence of several pro-inflammatory and immune proteins along with an enrichment in angiogenic receptors. Conclusions: We demonstrated the presence of EndoMT in human AT in obesity. EndoMT in vitro resulted in production of EV that transferred some of the functional and metabolic features to recipient naïve EC. This result suggests that functional and molecular features of EC that underwent EndoMT in vivo can be disseminated in a paracrine or endocrine fashion and may induce endothelial dysfunction in distant vascular beds. Abstract : Supplemental Digital Content is available in the text.